Effect of deferent levels of fertilizer 9DAP) in content of plant leaves from phenol compounds and (NPK) - Mohammed Dhary Yousif (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 10th Edition, 2019)
Carried out the experiment in the Republic of Iraq in the capital Baghdad and in the Dora district to study the effect of different levels of fertilizer (DAP) in content of plant leaves(Calotropis procera) in terms of phenolic compounds, as well as content (N, P, K), in pots where the soil used sandy silt collected from the shoulder of the Tigris River where contained soil 750g/ kg sand, 200 g/kg Clays, 50 g/ kg clay, average virtual soil density 1.1 Mega grams/m3,the average electrical conductivity (Ec) 1.8 ds/m, the degree of interaction (pH) 7.2, the concentration of nitrogen-ready 20 mg/kg ,soil and phosphorus ready mg /kg 15 and 145 ready-potassium mg /kg soil .the experiment included add four levels (100 . 200 . 300 . 400 ) kg / h of DAP fertilizer (18:46 N: P) to the publican seedlings which are Elected age of one year and using fully randomized design (CRD) and in three replications. in dated 10/15/2014. After the sample was taken leaves of the plant to assess the content of phenolic compounds (Gallic acid , Vanillic acid, Epicatechin , P-coumaric , Ferulic acid ,Queretin-3-ß-D- glucoside , Rutin)as well as total chlorophyll and (N, P, K).Results of statistical analysis showed the least significant difference (LSD) at a level of 5% higher than the level of fertilization 400 kg DAP /h on the rest of the levels followed by a level 300 and level 200.Where the increase in the rates of securities content of phenolic compounds, especially Epicatechin (48.72, 87.20, 137.18%) compared to the first level of 100 kg DAP / h sequentially with significant differences. The percentage increase in the stock of the content of p- coumaric (43.82, 85.39 and 92.13) % to the level of the second, third and fourth sequentially compared to the first level. As for (Ferulic acid, Queretin - 3Ø-D-glycoside, Rutin and Chlorophyll) in fourth level of 400 kg DAP /h has achieved the highest concentration content where the percentage increase (1050, 86, 164.81 and 40.47) % sequentially compared to the first level 100 kg DAP /h. Nitrogen, Phosphorus and Potassium, where the focus accounted for an increase of (80.99 and 155.00 and 65.38%) compared to the first level and sequentially. The results show that the plant () showed a steady and flexible response to the levels of fertilizer DAP, Increase the speed of absorption of key nutrients (N and P), to increase the readiness of those elements in the soil solution, increasing the shoot and root. Increase the efficiency of absorption of the major key elements (K, P, N) content and increase the stock of vehicles and phenolic acids and thus increase in the proportion of plant chlorophyll content.
Keywords: Q3; 330; Calotropis procera; phenolic compounds; dap fertilizer (N; P; K)